La crónica vorágine de Arturo Cova - Correa Soto, Carlos Mario (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
In this descriptive and interpretive article, we aim to show how Arturo Cova ‒José Eustasio Rivera’s alter ego‒ in the pages of the novel La vorágine (published in 1924), is constructed as a poet-chronicler through his own story and those of the supporting characters. We observe that several formal characteristics of the chronicle are prefigured here, both in the narrative style of reportage and in other contemporary non-fiction narratives.